Soil Health Management under Climate Change Scenario: A Framework for Future Agricultural Practices - Prakash R. Kadu (Journal of the Indian Society of Soil Science, 2026)
Climate change is a defining issue currently. A lot of significant long-term changes are happening in global climatic system which are visible all over the world. The direct solar radiations (enormous amount of heat/ energy) striking on earth’s surface is being trapped by Green House Gases (GHGs) like carbon dioxide (CO), methane (CH), nitrous oxide (N2O), hydrofluorocarbons (HFCs), etc., resulting in atmospheric temperature increase. Specifically, the CO levels are at peak and its concentration has reached up to 410 ppm at present, which is a principal cause of warming effect (Srinivasa Rao et al. 2019).